Malignant hypertensive retinopathy as a presenting sign of an occult dead fetus - Araújo J (Dove Medical Press, 2015)
Joana Araújo,1 João Tavares-Ferreira,1 Susana Penas,1,2 Luís Figueira,1,3 Flávio Prézia Paiva,1 Fernando Falcão-Reis1,2 1Ophthalmology Department, São João Hospital, 2Department of Sense Organs, 3Department of Pharmacology and Therapeutics, Faculty of Medicine, University of Porto, Porto, Portugal Abstract: We report one case of malignant hypertensive retinopathy as a presenting sign of fetal death in utero. Ophthalmic examination (including intravenous fluorescein angiography and optical coherence tomography) and obstetric and systemic evaluation were performed, providing a multidisciplinary approach. A 33-year-old overweight woman (body mass index 47 kg/m2) with no systemic or ocular known disease was admitted to our emergency department with a one-week history of bilateral vision loss and no systemic complaints. On examination, best corrected visual acuity was 1/10 in the right eye and 1/10 in the left eye. Anterior segment examination of both eyes was unremarkable. Ophthalmoscopic fundus findings included bilateral optic disc edema, diffuse cotton wool spots, intraretinal exudates, retinal hemorrhages, and multiple serous retinal detachments involving both maculae. Physical examination revealed a blood pressure of 220/ 110 mmHg. Further systemic workup revealed a previously unknown 35-week pregnancy with a dead fetus. An emergency cesarean section was performed. Pre-eclampsia is a life-threatening disorder for both mother and fetus. This case highlights the need to rule out pre-eclampsia in all women of childbearing age presenting with ocular signs of malignant hypertension, even without external signs of pregnancy. Keywords: hypertensive retinopathy, pre-eclampsia, vision loss